Microeconomic Thought in Islamic Scholarship: A Comparative Study of Abu Ubayd and al-Shaybani - R. Ira Laksana Dewi; Yadi Janwari; Dedah Jubaedah (STAI Al-Mas'udiyah, 2026)
This research examines the microeconomic theories of two influential Islamic scholars, Abu Ubayd and Al-Syaibani, as reflected in Kitab al-Amwal, Kitab al-Kasb, and al-Iktisab. The research addresses the limited comprehensive studies linking classical Islamic economic thought with its relevance to contemporary microeconomics. The objective is to examine their principles in the historical context, grounded in Sharia values, and assess their applicability to modern economic issues. Employing a qualitative-descriptive approach through library research, the study draws from primary and secondary sources with descriptive-analytical methods. The findings show that Abu Ubayd, while focusing on public finance, contributes micro-level concepts such as justice in wealth distribution, equitable taxation, public resource management, and the state’s role in societal welfare. In contrast, Al-Syaibani emphasizes the obligation to work (kasb) as an act of worship, classification of economic activities, fulfillment of basic needs, labor specialization, and ethical production and consumption aligned with maqasid al-shariah. Despite differing emphases, both scholars share the vision of establishing a just economic system rooted in Islamic values, offering insights for enriching contemporary Islamic microeconomic theory and guiding public policy and household economic behavior